2017
DOI: 10.18235/0000654
|View full text |Cite
|
Sign up to set email alerts
|

Skill Premium, Labor Supply and Changes in the Structure of Wages in Latin America

Abstract: work is licensed under a Creative Commons IGO 3.0 AttributionNonCommercial-NoDerivatives (CC-IGO BY-NC-ND 3.0 IGO) license (http://creativecommons.org/licenses/by-nc-nd/3.0/igo/ legalcode) and may be reproduced with attribution to the IDB and for any non-commercial purpose, as provided below. No derivative work is allowed.Any dispute related to the use of the works of the IDB that cannot be settled amicably shall be submitted to arbitration pursuant to the UNCITRAL rules. The use of the IDB's name for any purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…The results of Ferreira et al (2017) are similar to the ones reported by Fernández and Messina (2018) and Alvarez et al (2018). The first conducts a similar decomposition as Ferreira et al (2017), but uses a more restricted set of covariates.…”
Section: Education and Experience: Composition Vs Price Effectssupporting
confidence: 71%
See 1 more Smart Citation
“…The results of Ferreira et al (2017) are similar to the ones reported by Fernández and Messina (2018) and Alvarez et al (2018). The first conducts a similar decomposition as Ferreira et al (2017), but uses a more restricted set of covariates.…”
Section: Education and Experience: Composition Vs Price Effectssupporting
confidence: 71%
“…are not yet clear. Although strong evidence suggests that changes in the relative supply of skilled labor explain almost all the reduction in the skill premium, changes in the supply of potential experience explain only a limited amount of the variation in the experience premium, meaning that changes in demand must have played a role (Fernández and Messina, 2018). As for now, the literature has not investigated possible changes in the economy that favored younger workers in the period.…”
mentioning
confidence: 99%
“…The model uses the same elasticities in all three countries. Source: Fernández and Messina (2017). The dark orange line shows the observed evolution of the skill premium.…”
Section: The Market For Skills: Beyond Supply and Demand 77mentioning
confidence: 99%
“…Certainly, supply changes have been an important force behind recent changes in the schooling premium in Latin America and the Caribbean, but they are not the sole factor (Messina and Silva, 2016). Fernández and Messina (2017) study the supply effects of education and experience in the schooling and experience premiums of Argentina, Brazil and Chile. They consider two types of workers: skilled and unskilled.…”
Section: 7mentioning
confidence: 99%
See 1 more Smart Citation